2018
DOI: 10.1038/s41419-018-0398-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting PSMα-induced neutrophil necroptosis protects mice with MRSA pneumonia by blocking the agr system

Abstract: Given its high resistance, enhanced virulence, and high transmissibility, community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) pneumonia is highly associated with high morbidity and mortality. Anti-virulence therapy is a promising strategy that bypasses the evolutionary pressure on the bacterium to develop resistance. RNAIII-inhibiting peptide (RIP), as an accessory gene regulator (agr)-specific inhibitor, significantly restricts the virulence of S. aureus and protects infected mice from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 38 publications
3
41
0
Order By: Relevance
“…The tendency of neutrophils changes in MRSA-induced pneumonia was consistent to previous reports [36]. However, our study showed that the peak time of neutrophils elevation, 6 h after MRSA injection, was significantly earlier than that of Feng et al at 24 h. This may be related to that more neutrophils were released by bone marrow in the beginning of MRSA stimulation, then decrease in neutrophil may be associated with Phenol-soluble modulins (PSMs)-induced neutrophil necroptosis [19]. Collectively, these data suggested that hUMSCs treatment possibly reduced pneumonia symptoms via suppression of inflammation induced by MRSA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The tendency of neutrophils changes in MRSA-induced pneumonia was consistent to previous reports [36]. However, our study showed that the peak time of neutrophils elevation, 6 h after MRSA injection, was significantly earlier than that of Feng et al at 24 h. This may be related to that more neutrophils were released by bone marrow in the beginning of MRSA stimulation, then decrease in neutrophil may be associated with Phenol-soluble modulins (PSMs)-induced neutrophil necroptosis [19]. Collectively, these data suggested that hUMSCs treatment possibly reduced pneumonia symptoms via suppression of inflammation induced by MRSA.…”
Section: Discussionsupporting
confidence: 91%
“…At first, we established the rabbit pneumonia model, which was different from the previous experiments that focussed on disperse intratracheal administration in rodents [17–19]. Although different MRSA-infected animal models have been described previously [16,17,19], there were rarely animal models using implantation of MRSA quantitatively and directionally to special bronchus which mimic the course of lung infection occurred in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Quorum sensing of MRSA has attracted renewed attention in recent years as a novel treatment target, and several synthetic, peptide, and natural quorum sensing quenchers have been assessed ( Salam and Quave, 2018 ). However, only a few studies have progressed to in vivo MRSA pneumonia models ( Waters et al, 2017 ; Zhou et al, 2018 ), meaning that a detailed understanding of the role of the agr quorum sensing system in the pathology of MRSA pneumonia remains to be determined. Here, we could demonstrate that Pi Sup promoted MRSA proliferation, resulting in upregulation of toxin expression via quorum sensing, which may shed some light on the role of the quorum sensing system in MRSA pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, staphylococcal pore-forming toxins including α-toxin promote tissue damage and necroptotic cell death in immune and epithelial cells during lung infection ( 68 , 147 ). Moreover, S. aureus phenol-soluble modulins (PSM peptides) constitute potent catalysts of necroptosis as these cytolytic peptides activate necroptotic death of host phagocytes via induction of MLKL phosphorylation, ultimately leading to exacerbated outcomes of staphylococcal pulmonary infections ( 71 ). Although most of these toxins have distinct receptors, all variants exhibit potent immunomodulatory properties that together trigger assembly of the necrosome, and subsequent necroptotic cell death ( 68 , 148 , 149 ).…”
Section: Exploitation Of Necroptotic Signaling By Staphylocmentioning
confidence: 99%
“…Also, in vivo blockade of c-Jun N-terminal kinases (JNK1 and JNK2), both of which are known to trigger TNF- and TLR-induced necroptotic cell death, or genetic ablation of the peroxisome proliferator-activated receptor α (PPARα), a ligand-activated transcription factor and suppressor of NF-κB activation, rescued mice from fatal staphylococcal lung disease, even under conditions that mimic bacterial superinfections ( Table 2 ) ( 112 , 113 ). Zhou et al exploited RNAIII-inhibiting peptide as an anti-virulence therapeutic approach to prevent PSM- and necroptosis-dependent lung injury in mice nasally infected with CA-MRSA strain USA300 ( 71 ). RNAIII is the effector of accessory gene regulator (Agr) and RNA-III inhibiting peptide blocks S. aureus quorum sensing and biogenesis of PSMs toxins during acute lung infection ( 71 ).…”
Section: Exploitation Of Necroptotic Signaling By Staphylocmentioning
confidence: 99%